Control of Rail-Road PI-Hub: The ORCA Hybrid Control Architecture - Vo, Nhat-Vinh; Berger, Thierry; Bonte, Thérèse; Sallez, Yves (HAL CCSD, 2018)
International audience In the innovative field of Physical Internet, the development of efficient PI-cross-docking hubs (denoted PI-hub) allowing quick, efficient and flexible transfer of containers is a cornerstone. The paper addresses the control of such facilities and focuses more particularly on a “rail-road” PI-hub. After a review of the related control issues, an instance of the ORCA hybrid control architecture is proposed. The focus is held on the PI-containers routing in a perturbed environment. More specifically, predictive and reactive routing strategies are presented. The simulation environment, protocol and results are then detailed.